Anti-tumoral activity of imidazoquines, a new class of antimalarials derived from primaquine - Fernandes, Iva (2015)
The growth inhibitory activity of imidazoquines, antimalarial imidazolidin-4-ones derived from primaquine, on human cancer cell lines HT-29, Caco-2, and MCF-7 has been evaluated. Primaquine, N-dipeptidyl-primaquine derivatives, and other quinolines have been included in the study for comparison purposes. Primaquine and some of its derivatives were significantly active against the MCF-7 human breast cancer cell line, so these compounds might represent useful leads targeted at the development of novel specific agents against breast cancer. Conversely, all compounds were generally inactive against HT-29, with only one of the imidazoquines having IC50 below 50 mu M. Activities against the Caco-2 cell line were modest and did not follow any defined trend. (C) 2009 Elsevier Ltd. All rights reserved.. - Portuguese Foundation for Science and Technology (FCT) [PTDC/QUI/65142/2006, PTDC/QUI/65501/2006, CONC-REEQ/275/QUI, REDE/1517/RMN/2005, SFRH/BPD/48345/2008, SFRH/BD/38883/2007]. - Thanks are due to the Portuguese Foundation for Science and Technology (FCT) for financial support through Project Grants PTDC/QUI/65142/2006, PTDC/QUI/65501/2006, CONC-REEQ/275/QUI and REDE/1517/RMN/2005. N.V. and I. F. thank FCT for, respectively, Post-Doc Grant SFRH/BPD/48345/2008 and Ph.D. Grant SFRH/BD/38883/2007.